Pengaruh Video Advertising Tokopedia Versi “Jadikan Ramadan Kesempatan Terbaik” Terhadap Respon Afektif Khalayak - Jennifer Olivia; Sylvie Nurfebiaraning (Universitas Serang Raya, 2019)
Many advertisers believe that consumer emotions are better at advertising effectiveness,because if you only sell brands there will be no striking differences with competitors orcompetitors. The way to attract the consumer attentions, to use the products and brands ofthe company is to advertise and make the audience like the advertisement. One of theadvertising videos